Efficiency of Online Learning and Difficulties Encountered: Case of Albanian Students - Shoraj, Dritan; Kadiu, Esra (European Journal of Social Science Education and Research, 2024)
The end of last century and the beginning of 21st century marked a significant evolution in information technology and virtual world as a whole, which influenced and dictated the way of living and working around the world, especially in the most developed countries. Thanks to this development, it was possible to cope successfully and continuously during Covid 19 pandemic. Education as one of the strategic and most sensitive sectors, due to Covid 19 pandemic, faced the online learning platform around the globe. In the US and in some developed EU countries, the online learning platform has been a practice applied in the past. However, for many other countries, including Albania, the online learning platform was something new that students and faculty had to face at any rate. Yet, are stakeholders ready to face the online learning platform? This study has analyzed some of the obstacles faced by students, upon the implementation of the online platform. It will be observed whether the efficiency of online learning will have the same efficiency as classical learning. These many other questions will be answered through an empirical and theoretical analysis that was made possible through an online survey, which surveyed 1672 students from all private and public universities operating in the Albanian territory. Multi-factor analysis will be performed through SPSS program, ANOVA test, and Chi-square (x2). Finally, some conclusions finalize this scientific study.